OC-055 What is the true incidence of metachronous colorectal liver metastases? evidence from the UK FACS (follow-up after colorectal surgery) trial (ISRCTN: 41458548). (28th May 2012) - Pugh, S; Fuller, A; Rose, P; Perera-Salazar, R; Mellor, J; George, S; Mant, D; Primrose, J
Abstract : Introduction: Detecting patients with resectable metachronous colorectal liver metastases and performing potentially curative surgery is commonly cited as a reason for following up patients with completely resected colorectal cancer. However, the actual incidence of metachronous metastasis in fully staged and optimally treated colorectal cancer patients is not known with certainty. The FACS trial, the UK national trial on colorectal cancer follow-up, provided an opportunity to address this question. Methods: Patients were recruited to the trial following potentially curative resection of the primary colorectal cancer (Dukes' stages A–C, (I–III)). Complete evaluation by CT chest, abdomen and pelvis and a normal CEA (carcinoembryonic antigen) after surgery or adjuvant chemotherapy were prerequisites to trial entry. Patients were randomised in a 2×2 trial design of intensive imaging vs minimal CT imaging and CEA vs no CEA measurement. Follow-up data including site of recurrence and further surgery has been collected prospectively. An observational analysis has been performed on the entire cohort at a median follow-up of 54 months. Results: A total of 1260 patients were recruited of which 22% were in Dukes' stage A (I), 48% stage B (II), and 30% stage C (III) (remainder awaiting data clarification). At follow-up 85.6% of patients were alive without recurrence (stage A 90.9%, stage B 86.7%, stage C 80.4%). Of the 178 recurrences the majority were loco-regional or at multiple sites. Liver metastases were found in 72 (40% of patients with recurrence) and 45 (25%) had liver only disease. A potentially curative liver resection was performed in 35 patients (20%). Thus at a median follow-up of 54 months 5.7% of the study cohort had metachronous metastases in the liver. In 3.6% of the cohort the disease was confined to the liver and 2.8% went on to have a potentially curative liver resection. Conclusion: These preliminary data demonstrate that the incidence of metachronous liver metastasis in fully staged patients with colorectal cancer appears to be low. Furthermore due to the often multi-site nature of the recurrence only a small proportion of patients can be cured. Thus very intensive follow-up strategies to detect colorectal liver metastases are unlikely to be cost effective. These data emphasise the importance of fully staging the liver at the time of treatment of the primary disease. Competing interests: None declared.